POLA PENYEBARAN GAS NO 2 DI UDARA AMBIEN KAWASAN UTARA KOTA SEMARANG PADA MUSIM KEMARAU MENGGUNAKAN PROGRAM ISCST3 - Hadiwododo, Mochtar; Huboyo, Haryono Setiyo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2006)
North  district  of  Semarang  City  is  an  area  characterized  by  dense  population, congested transportation, and high  industry activities.  Urban activities in this area are predicted produce enourmous pollutant  one  of  them is  NO 2 .    This  gas  is  hazardous  for  human  health, and can cause death even that concentration exceed standard level 150 µgr/m3.  Inventory emission is used to identify sources that produce NO 2  gas and quatify the concentration.  ISCST3 program was used as a tool to recapitulate the dispersion  of NO 2  gas in ambient from it sources to the potent receptor. Combinated with  Surfer program, it result were easily be visualized trough NOx isopleth  contour  overlaid  to  land used  map.  The  result  of  this  observation  showed  that  total emission  of  NO 2   gas  in  area observation  is  0,001445  ton/year  where  is  transportation contributes 91,68 %, followed by industry 8,31 %, and domestic 0,01 %.  Dispersion pattern of NO 2   gas  in  ambient  is  mainly  affected  by calm  condition  of  wind  making  NO 2   gas  is concentrated in 3 regions i.e Pindrikan Kidul, Peterongan, and Tambakrejo.